Vinasse from Sugarcane Ethanol Production: Better Treatment or Better Utilization? - Rodrigues Reis, Cristiano E.; Hu, Bo (Frontiers in Energy Research, 2017)
Ethanol production from sugarcane in Brazil is a well-established industry, with relatively simple operations and high yield. The ethanol primarily serves as a renewable fuel blending with gasoline and diesel to increase the energy security in Brazil. Several environmental concerns are emerged around the by-products from this industry. Vinasse, the liquid fraction generated from the rectification and distillation operations of ethanol, is a sulfur-rich, low pH, dark-colored, and odorous effluent, produced at volumes as high as 20 fold of ethanol. Traditional wastewater treatments, such as bioprocessing, advanced oxidative processes, anaerobic digestion, and chemical-based processes, have been applied to vinasse management. Despite most of its utilization being in fertirrigation practices, vinasse may represent a key factor in enhancing profitability and environmental outcomes of a sugarcane-to-ethanol plant. The application of some upgrade solutions to sugarcane-derived vinasse may represent additional sources of energy, production of animal feed components, and reduction in water consumption within a plant. The use of mature technologies, yet not widespread in the sugarcane-to-ethanol industry, could help attenuate environmental concerns. Oxidation and chemical processes, anaerobic digestion, and microbial fermentation have been presented as alternative impactful alternatives to (i) reduce its organic and mineral load, converting it to a feedstock with fewer environmental applications when applied as fertilizer, and (ii) to convert organic matter and nutrients to a nutritious biomass, simultaneously increasing water reclamation potential by plants. This mini-review article provides a critical and comprehensive summary of the alternatives developed or under development to vinasse management.